2016
DOI: 10.1152/physiol.00051.2015
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Roles of Fluctuation-Driven Mechanotransduction in Cell Function

Abstract: Cells in the body are exposed to irregular mechanical stimuli. Here, we review the so-called fluctuation-driven mechanotransduction in which stresses stretching cells vary on a cycle-by-cycle basis. We argue that such mechanotransduction is an emergent network phenomenon and offer several potential mechanisms of how it regulates cell function. Several examples from the vasculature, the lung, and tissue engineering are discussed. We conclude with a list of important open questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 141 publications
(160 reference statements)
1
19
0
Order By: Relevance
“…These same effects are seen in other collagenous soft tissues[28], and support the notion that IOP transients play an important role in the connective tissue remodeling signaling cascade. In addition, changes in ocular coat stiffness affect the magnitude of IOP transients[29], insofar as the eye is an elastic pressure vessel that can expand and contract to absorb some of the energy associated with transient events such as blink, saccade, and vascular pulse.…”
Section: Cellular Basis Of Ocular Connective Tissue Remodelingsupporting
confidence: 82%
“…These same effects are seen in other collagenous soft tissues[28], and support the notion that IOP transients play an important role in the connective tissue remodeling signaling cascade. In addition, changes in ocular coat stiffness affect the magnitude of IOP transients[29], insofar as the eye is an elastic pressure vessel that can expand and contract to absorb some of the energy associated with transient events such as blink, saccade, and vascular pulse.…”
Section: Cellular Basis Of Ocular Connective Tissue Remodelingsupporting
confidence: 82%
“…To explain these results, we first consider the amount of mechanical energy communicated to the cell during stretching. Assuming that cells can be considered a simple linearly elastic material, we have shown that the energy during variable stretching is related to the fluctuations in cycle-by-cycle amplitude 23 . The energy density during variable stretch (E VS ) can be written in the following form:…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the external mechanical environment is invariably noisy due for example to beat-to-beat blood pressure variability (BPV). Consequently, cells and their mitochondria also respond to fluctuations in mechanical factors, a process called fluctuation-driven mechanotransduction (FDM) 23 . Indeed, we recently reported that ATP production, monitored via the mitochondrial membrane potential, was maintained at a high level in vascular smooth muscle cells (VSMCs) when they were exposed to a variable-amplitude cyclic stretch pattern mimicking normal BPV compared with monotonous constant-amplitude cyclic stretch 24 .…”
mentioning
confidence: 99%
“…Integrin receptors perform both structural and mechanosensing signalling functions within cell-matrix adhesions. Integrins form heterodimers, consisting of an alpha and beta subunit [62] and are structurally comprised of an extracellular ligand-binding domain, which binds the ECM, and a cytosolic domain, which is anchored to the actin cytoskeleton [63] . Before transducing intracellular tension to the ECM, the integrin receptors must mature via the recruitment of further integrin receptors as well as other cytoskeletal components [64] .…”
Section: Cell-matrix Adhesionsmentioning
confidence: 99%
“…Before transducing intracellular tension to the ECM, the integrin receptors must mature via the recruitment of further integrin receptors as well as other cytoskeletal components [64] . Talin and alpha-actinin bind directly to the cytosolic domain of integrin and talin binding promotes the recruitment of additional components to cell matrix adhesions, including vinculin, paxillin and focal adhesion kinase [62,65] . Vinculin consists of 3-stuctural regions known as the head, neck and tail domain [66] .…”
Section: Cell-matrix Adhesionsmentioning
confidence: 99%